Transformation of Polyoxometalate into 3D Porous Li‐Containing Oxide: A Case Study of γ‐LiV2O5 for High‐Performance Cathodes of Li‐Ion Batteries. Issue 10 (18th April 2019) - Bayaguud, Aruuhan; Zhang, Zhibo; Geng, Maoning; Fu, Yanpeng; Yu, Yan; Zhu, Changbao
Abstract: The development of cathode materials with high Li storage capacity and fast Li‐ion diffusion kinetics is considered to be a promising way to extend the energy and power densities of Li‐ion batteries (LIBs). As potential high‐capacity cathode materials for LIBs, polyoxometalates (POMs) suffer greatly from inherent drawbacks. Therefore, another possibility for the application of POMs in LIBs is shown, which is to transform POMs into relevant 3D porous Li‐containing oxides. Here, a unique 3D porous γ‐LiV2 O5 film is successfully prepared by combining the electrostatic spray deposition technique and the POM as a precursor. Outstanding high capacity with stable cycling performance and excellent rate capability is realized based on 3D porous nanostructure and thin‐film morphology, which effectively facilitate the transport of both lithium ion and electron. Moreover, this work demonstrates the feasibility of achieving high‐performance metal oxide cathode by the transformation of POMs and also shows the superiority of γ‐phase over α‐phase as a starting cathode material in LIBs as well. Abstract : A high‐performance 3D porous γ‐LiV2 O5 film cathode for lithium‐ion batteries is fabricated by combining electrostatic spray deposition technique and direct polyoxometalate transformation reaction. A power density output of 28.3 kW kg −1 with an energy density output of 558 Wh kg −1 is available due to the outstanding high capacity and rate capability of this γ‐LiV2 O5 cathode.